Temporomandibular joint trauma and disability assessment - A longitudinal exploratory study. (August 2021) - Figueiredo, Cristina; Afonso, Américo; Caramelo, Francisco; Corte-Real, Ana
Abstract: Background: Orofacial trauma can encompass, isolated or not, several anatomical regions, namely facial, dental and temporomandibular joint (TMJ), one of the most complex joints in the human body. Evidence-based knowledge in the field of TMJ trauma and in temporomandibular joint disorders (TMD) diagnosis and treatment, provides the necessary data for medico-legal assessment. Objective: The aim of this study is to bring up epidemiological data referring to TMJ injuries and sequelae, in order to present a medico-legal approach of TMJ disability. Methods: An observational longitudinal exploratory study was performed in the database of the National Institute of Legal Medicine and Forensic Sciences, Portugal, between 2000 and 2017, regarding inclusion and exclusion criteria.Statistical significance was set as P ‹0.05, Fisher's exact test, Binomial test and Goodman and Kruskal's test were used. Results: Post-traumatic orofacial reports (n = 2622) included 234 TMJ-injury and 149 TMJ-sequelae.Epidemiological data was presented regarding age, gender, professional status and etiology. There was a statistically significant association between TMJ injury and TMJ sequela, despite a weak relation (ƛ = 0.170). No statistically significant association was identified between TMJ-injury/TMJ-sequelae and the professional status, etiology. Conclusion: The TMJ sequela group is smaller than the TMJ-injury, reflecting that 2/3 of the injuries have been cured without a monetary compensation value and without Health costs. The association between TMJ injury and TMJ sequelae reinforces the necessity of preventive measures in TMJ trauma, namely in physical violence context and in medico-legal impairment. Highlights: A Portuguese database of medico-legal reports allowed an observational longitudinal exploratory study. An upgrade to disability assessment for temporomandibular joint trauma was presented in several statistical associations. Preventive practices against violence must be acquired for the general population. The medico-legal expertise must consider organic, functional and situational sequelae of temporomandibular joint trauma.